Age and Achalasia: How Does Age Affect Patient Presentation, Hospital Course, and Surgical Outcomes?. Issue 9 (September 2017) - Downs, Darrell J.; Jadick, Giavanna; Swaid, Forat; Ross, Sharona B.; Rosemurgy, Alexander S.
Heller myotomy is the "gold-standard" therapy for achalasia, alleviating symptoms by defunctionalizing the lower esophageal sphincter mechanism. Observation has suggested many differences between young and old patients with achalasia, raising the question: is achalasia in younger patients a different disorder than it is in older patients? This study was undertaken to answer this question. With Institutional Review Board approval, 648 patients undergoing laparoscopic Heller myotomy from 1992–2016 were prospectively followed up. Patients self-assessed symptom frequency/severity preoperatively and postoperatively using a Likert scale; 0 (never/not bothersome) to 10 (always/very bothersome). Before myotomy, frequency/severity of many symptoms (e.g., "dysphagia, " "chest pain, " and "regurgitation") inversely correlated with age (P < 0.01 each). Symptom duration and the number of previous abdominal operations correlated with age, as did intraoperative complications (e.g., gastrotomy), postoperative complications (e.g., atrial fibrillation), and length of stay (P < 0.01 for each). Patients experienced amelioration of all symptoms queried, regardless of age (P < 0.01 each). Age did affect outcome because older patients had less frequent and severe symptoms. Age did not affect improvement of symptoms (e.g., dysphagia) (i.e., differences between preoperative and postoperative scores) (P = 0.88). Age did not influence symptom resolution or patient satisfaction (P = 0.98 and P = 0.15, respectively). The presentation with achalasia, hospital course, and outcome after myotomy are significantly impacted by age, whereas patient improvement after myotomy is constant independent of age. Younger and older patients have different presentations, experiences, and outcomes; these patients seem to have "different disorders", but Heller myotomy provides similar significant amelioration of symptoms independent of age.